1994
DOI: 10.2737/nc-rp-320
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of <i>Populus</i> in short-rotation intensive culture plantations in the north-central U.S.

Abstract: The policy of the United States Department of Agriculture Forest Service prohibits discrimination on the basis of race, color, national origin, age, religion, sex, or disability. familial status, or political affiliation. Persons believing they have been discriminated against in any Forest Service related activity should write to: Chief,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…The selected clones represented a range of hybrid parentages among the Aegerios and ¹acamahaca sections of the genus Populus. They included "ve frequently planted P. deltoides x P. nigra clones and six other clones that have performed well in the "eld under short rotation culture (Hansen et al, 1994). Isoprene emission rates measured at PAR of 1000 mol m\ s\ and 253C were all high (clonal means ranging from 46 to 91 g(C) g\ h\; Fig.…”
Section: Genetic Ewectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected clones represented a range of hybrid parentages among the Aegerios and ¹acamahaca sections of the genus Populus. They included "ve frequently planted P. deltoides x P. nigra clones and six other clones that have performed well in the "eld under short rotation culture (Hansen et al, 1994). Isoprene emission rates measured at PAR of 1000 mol m\ s\ and 253C were all high (clonal means ranging from 46 to 91 g(C) g\ h\; Fig.…”
Section: Genetic Ewectsmentioning
confidence: 99%
“…Populus euramericana (DN34), probably the most widely planted clone in the North Central region of the US (Hansen et al, 1994), emitted over 84 g(C) g\ h\of isoprene ( '150 g(C) g\ h\ at 303C); and Populus tremuloides (trembling aspen), which occupies over 15 million hectares of forest land in the northern USA, had isoprene emission rates of over 77 g(C) g\ h\. Aspen with its &&high'' isoprene emission rates is also a very sensitive species to ambient levels of tropospheric ozone (Coleman et al, 1995).…”
Section: Alnus Rugosamentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen of the seventeen sites for the current study were selected from two regional networks of hybrid poplar clone and yield trials established in the north-central United States during 2000 to 2001 (10-year-old plantations) [27,37] and 1988 to 1991 (20-year-old plantations) [38][39][40]. The remaining two sites (15-year-old plantations) were established in 1995 as part of the woody biomass feedstock development program at Iowa State University (Figure 1).…”
Section: Site and Clone Selectionmentioning
confidence: 99%
“…Unfortunately, results of clonal trials in North and South Dakota, Minnesota, and Wisconsin suggested that few NE hybrids combine all the characteristics needed in a modern commercial cultivar. In fact, all but one of the hybrids have been rejected h m further trials because of poor growth, disease susceptibility or instability and are no longer recommended for planting in the north-central U.S. (Hansen et al 1994).…”
Section: Introductionmentioning
confidence: 99%